Exploring Clinical Decision-Making Competencies of Emergency Nurses in Trauma Care in Indonesia: Qualitative Study - Saharuddin Saharuddin; Elly Nurachmah; Masfuri Masfuri; Dewi Gayatri; Amelia Kimin; Muhammad Sakti; Sanisah Binti Saidi; Sri Yona (Asian/Pacific Island Nursing Journal, 2025)
Abstract BackgroundClinical decision-making is vital for emergency nurses, especially in trauma care that requires swift, accurate actions. In Indonesia, where resources are limited, little is known about how nurses manage such challenges. ObjectiveThis study aimed to explore the clinical decision-making competencies of emergency nurses in trauma care, focusing on challenges, strategies, and influencing factors. MethodsThis was a qualitative study using semi-structured interviews with 16 emergency nurses, complemented by observations and document analyses. Data were analyzed thematically, with triangulation, thereby ensuring validity. ResultsSix key themes emerged: (1) recognize cues; (2) analyze cues; (3) prioritize hypothesis; (4) generate solutions; (5) take actions; and (6) evaluate outcomes. These highlight the adaptive and multidimensional nature of decision-making in emergencies. ConclusionsThe decision-making of emergency nurses integrates analysis, prioritization, collaboration, and reflection. Enhanced training, such as simulation-based learning, and addressing systemic barriers can improve competencies. Policymakers should provide adequate resources and robust standards to support nurses under pressure.